Kinerja Petugas Kesehatan dalam Upaya Menurunkan Angka Kejadian Demam Berdarah Dengue di Puskesmas Kota Jambi - Rumita Ena Sari; Fransiska Sitepu; Arnild Augina Mekarische; Hubaybah Hubaybah; Rinaldi Daswito; Evy Wisudariani (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2021)
In Jambi Province, the morbidity rate of Dengue Hemorrhagic Fever (DHF) has increased for three consecutive years with a mortality rate of 0.74%. This study aimed to determine the performance of health workers to reduce the incidence of dengue fever at the Jambi City Health Center in 2020. This study used a cross-sectional design with several respondents 80 officers, the sampling technique used total sampling. The instrument in this study used a questionnaire. Data analysis using Chi-square test. The results showed that there was a significant relationship between the length of work (OR = 0.184), facilities and infrastructure (OR = 1.977), supervision (OR = 2.118), and superior support (OR = 2.029) with the performance of health workers, and there was no significant relationship between the last education (OR=1.152) and reward (OR=1.472) with the performance of health workers. Health officers DHF program are expected to maximize services such as environmental health inspections and PSN 3M counseling as well as increase supervision of the community so that they can participate in the prevention of DHF, namely by forming Jumantik cadres, maximizing outreach and outreach with the community, and fostering community self-hygiene.